2019
DOI: 10.1213/ane.0000000000003339
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Admission After the Implementation of an Enhanced Recovery After Surgery Pathway for Minimally Invasive Gynecologic Surgery

Abstract: We were able to define predictors of admission for patients having LH/RAH managed with an ERAS pathway. Increased ASA physical status, being African American, and increased length of procedure were significantly associated with admission after LH/RAH performed under an ERAS pathway. In addition, the incidences of urgent clinic and ER visits, readmissions, and reoperations within 90 days of surgery were similar for patients who were discharged on the day of surgery compared to those admitted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 34 publications
1
53
0
Order By: Relevance
“…16 Same-day discharge after laparoscopic and robotic hysterectomy has been described in many studies, the rates being between 27%-90%. 9,11,[17][18][19] In the study by Keil et al, 11 the length of hospital stay decreased from 34 hours to 20 hours. Minig et al 19 reported a median length of hospital stay of 22.7 hours.…”
Section: Discussionmentioning
confidence: 94%
“…16 Same-day discharge after laparoscopic and robotic hysterectomy has been described in many studies, the rates being between 27%-90%. 9,11,[17][18][19] In the study by Keil et al, 11 the length of hospital stay decreased from 34 hours to 20 hours. Minig et al 19 reported a median length of hospital stay of 22.7 hours.…”
Section: Discussionmentioning
confidence: 94%
“…ERAS has been of considerable interest to the field of medicine in recent years [2]. ERAS protocols were first applied in colorectal surgery [2], expanding gradually to obstetrics and gynaecology [3], urology [4], and pelvic surgery [5]. Multimodal perioperative care played a vital role in the ERAS protocols that were based on ERAS society guidelines [6].…”
Section: Introductionmentioning
confidence: 99%
“…Initially proposed by Danish surgeon, Henrik Kehle, ERAS is a multi-professional and multidisciplinary approach to the care of the surgical patient in order to obtain a rapid recovery after surgical intervention (11). While the initial efforts focused on colorectal surgery, the basic principles now been adopted to multiple surgical specialties (6,(12)(13)(14). ERAS protocols have been shown to be particularly bene cial for the elderly people who often have co-morbidities and run a higher risk of surgical complications.…”
Section: Discussionmentioning
confidence: 99%